Effects of layer shift and yarn path variability on mechanical properties of a twill weave composite - Matveev, Mikhail Y.; Long, Andrew C.; Brown, Louise P.; Jones, I. Arthur (Sage Journals, 2016)
Experimental and numerical analysis of a woven composite were performed in order to assess the effect of yarn path and layer shift variability on properties of the composite. Analysis of the geometry of a 12K carbon fibre 2×2 twill weave at the meso- and macro-scales showed the prevalence of the yarn path variations at the macro-scale over the meso-scale variations. Numerical analysis of yarn path variability showed that it is responsible for a Young’s modulus reduction of 0.5% and CoV of 1% which makes this type of variability in the selected reinforcement almost insignificant for an elastic analysis. Finite element analysis of damage propagation in laminates with layer shift showed good agreement with the experiments. Both numerical analysis and experiments showed that layer shift has a strong effect on the shape of the stress-strain curve. In particular, laminates with no layer shift tend to exhibit a kink in the stress-strain curve which was attributed solely to the layer configuration.